Can immunodiagnostics help in the evaluation of interstitial lung diseases? - Dworacki, Grzegorz (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
The current diagnosis of interstitial lung diseases needs direct evaluation of lung tissue by means of histopathologic techniques. However, today important data in order to establish the right diagnosis and further monitoring of patients can also be obtained – very quickly, within a few hours – using flow cytometry evaluation of BAL (bronchoalveolar lavage). The standard flow cytometry immunophenotyping of cells present in BAL specimens include mainly evaluation of lymphocyte subpopulations and their state of activation. This technique is especially helpful in differential diagnosis of atypical inflammations, histiocytoses and lymphomas. Patients’ serum should also be screened for the presence of those types of autoantibodies which are often associated with pathogenesis of interstitial lung diseases.